Lipidation of small GTPase Cdc42 as regulator of its physiological and pathophysiological functions - Wirth, Alexander; Ponimaskin, Evgeni (Frontiers in Physiology, 2023)
The protein cell division cycle 42 (Cdc42) is a small GTPase of the Rho family regulating a plethora of physiological functions in a tissue, cell and subcellular-specific manner via participating in multiple signaling pathways. Since the corresponding signaling hubs are mainly organized along the cellular membranes, cytosolic proteins like Cdc42 need to be properly targeted and held at the membrane. Here, lipid modifications come into play: Cdc42 can be associated with membranes by different lipid anchors including prenylation (Cdc42-prenyl) and palmitoylation (Cdc42-palm). While Cdc42-prenyl is ubiquitously expressed, Cdc42-palm splicing variant in mainly expressed in the brain. Mechanisms underlying Cdc42 lipidation as well as its regulation are the main topic of this review. Furthermore, we will discuss the functional importance of Cdc42 lipid modifications with the focus on the role of different lipids in regulating defined Cdc42 functions. Finally, we will provide an overview of the possible implementation of Cdc42 lipidation in pathological conditions and different diseases.